Profitability and Discretionary Accrual through Supply Chain Management: Evidence of Manufacturing Firms using GMM Estimates in Indonesia - Muhammad Haykal; Erlina Erlina; Azhar Maksum; Iskandar Muda (International Journal of Supply Chain Management, 2020)
Abstract – This study examines supply chain power in the context of real earnings management. Accrual-based models are often used to examine the motives of managers in conducting discretionary accruals. Discretionary accruals by managers has a very broad impact and may mislead users of financial statements. This study analyses and examines the effect of company profitability on discretionary accruals, especially in emerging markets in Indonesia. This empirical study samples manufacturing sector companies listed on the Indonesia Stock Exchange from 2006 to 2016 and uses dynamic models with Generalised Method of Moments (GMM) estimation. This paper finds that the motives for signalling managers still influences the existence of discretionary accruals, and ROA, PBV, and EPS have a positive and significant effect on discretionary accruals. These findings prove that managers engage in discretionary accrual when reporting the profitability of the company. Leverage negatively affects discretionary accrual and the control mechanism of the current debt even though the effect is marginal. This study only examines the profitability motives of managers in conveying information to outsiders, and acknowledges that discretionary accruals may be influenced by variables beyond this study.